2018
DOI: 10.1111/fme.12287
|View full text |Cite
|
Sign up to set email alerts
|

High genetic diversity and lack of pronounced population structure in five species of sympatric Pacific eels

Abstract: Understanding the population structure of tropical anguillids residing in the Pacific is vital for their conservation management. Here, the population genetic structure of five sympatric freshwater eels (Anguilla marmorata Quoy & Gaimard, A. megastoma Kaup, A. obscura Steindachner, A. reinhardtii Günther and A. australis Richardson) across 11 western South Pacific (WSP) islands was investigated based on partial nucleotide sequences of the mtDNA control region and the nuclear GTH2b genes of 288 newly collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 75 publications
1
7
0
Order By: Relevance
“…Based on the results of morphological and genomic PCA (Fig. 1, Supplementary Figures 3,5), analyses with ADMIXTURE (Supplementary Figure 7) and fineRADstructure (Supplementary Figure 8), and previous reports (Schabetsberger et al, 2015; Gubili et al, 2019), we suspected that our dataset included recent hybrids between four species pairs: A. marmorata and A. megastoma, A. marmorata and A. obscura, A. megastoma and A. obscura , and A. marmorata and A. interioris. To verify these putative hybrids, we determined sites that were fixed in each of the four species pairs, considering only the “core”-group individuals for A. marmorata, A. megastoma , and A. obscura (see section “Morphological analyses”; 73, 26, and 26 individuals, respectively) and the three available individuals for A. interioris (Supplementary Table 1).…”
Section: Methodsmentioning
confidence: 84%
See 1 more Smart Citation
“…Based on the results of morphological and genomic PCA (Fig. 1, Supplementary Figures 3,5), analyses with ADMIXTURE (Supplementary Figure 7) and fineRADstructure (Supplementary Figure 8), and previous reports (Schabetsberger et al, 2015; Gubili et al, 2019), we suspected that our dataset included recent hybrids between four species pairs: A. marmorata and A. megastoma, A. marmorata and A. obscura, A. megastoma and A. obscura , and A. marmorata and A. interioris. To verify these putative hybrids, we determined sites that were fixed in each of the four species pairs, considering only the “core”-group individuals for A. marmorata, A. megastoma , and A. obscura (see section “Morphological analyses”; 73, 26, and 26 individuals, respectively) and the three available individuals for A. interioris (Supplementary Table 1).…”
Section: Methodsmentioning
confidence: 84%
“…Sampling localities included South Africa (AFC: n = 16), Swaziland (AFS: n = 1), Mayotte (MAY: n = 18), Réunion (REU: n = 10), Indonesia (JAV: n = 30), Philippines (PHC/PHP: n = 58), Taiwan (TAI: n = 30), Bougainville Island (BOU: n = 30), Solomon Islands (SOK/SOL/SON/SOR/SOV: n = 31), Vanuatu (VAG: n = 79), New Caledonia (NCA: n = 45), Samoa (SAW: n = 71), and American Samoa (SAA: n = 38). Sampling was performed as described by Schabetsberger et al (2015) and Gubili et al (2019), targeting elvers, yellow eels, and silver eels by electrofishing and with handnets in estuaries, rivers, and lakes. Small fin clips were extracted from the pectoral fin of each specimen and stored in 98% ethanol, to be used in subsequent genetic analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Habitat loss (Bevacqua et al ., ) as well as oceanic changes (Drouineau et al ., ) are considered to potentially influence population size of A. anguilla . Also comparable demographic histories of Atlantic A. anguilla and A. rostrata (Jacobsen et al ., ) and western South Pacific A. marmorata , Anguilla megastoma Kaup 1856, Anguilla obscura Günther 1972 and Anguilla reinhardtii Steindacher 1867 (Gubili et al ., ) have been described, albeit at time scales of 100–3000 kBP. The molecular rates used in these studies ranged from 1% to 5%, but the authors acknowledge that datings of the events probably were substantially overestimated (Jacobsen et al ., ), since time dependency allows for molecular rates up to 25% for events younger than 200 kBP (Burridge et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Gubili et al. () examined genetic structure of Anguilla marmorata Quoy & Gaimard, A. megastoma Kaup, A. obscura Steindachner, A. reinhardtii Günther and A. australis Richardson across 11 western South Pacific islands, revealing no evidence for distinct geographic clines or barriers in any of the species across the study area, but a new possible occurrence of A. interioris Whitley on Bougainville Island.…”
Section: Mechanisms For Translationmentioning
confidence: 99%
“…Understanding the oceanic migration behaviour and population structure of tropical anguillids residing in the Pacific, a very poorly understood region, is vital for their conservation and management. Gubili et al (2019) (2019) reported European silver eel escapement from a German regulated river at 63%. Further, Bolland et al (2019) found that about 4 in 10 migrating silver eels were blocked by pumping stations, with others delayed for several days.…”
Section: Mechanis Ms For Tr Ans L Ationmentioning
confidence: 99%